Pharmacodynamics, Network Pharmacology, and Pharmacokinetics of Chinese Medicine Formula 9002A in the Treatment of Alzheimer’s Disease - Tang, Chunlan; Fang, Zhiling; Chu, Donghui; Zhang, Lulu; Tang, Yuqing; Zhou, Jinyue; Fang, Rui; Ying, Jiaming; Wang, Fang; Zhou, Yuping; Xu, Chunshuang; Wang, Qinwen (Frontiers in Pharmacology, 2022)
Alzheimer's disease (AD) is a common and serious neurodegenerative disease in the elderly, whereas the treatment of AD is still lack of rational drugs. In this paper, the active constituents and targets of the self-developed Chinese medicine Formula 9002A in the treatment of AD was investigated from three aspects: pharmacodynamics based on cell and animal experiments, network pharmacology analysis, and pharmacokinetic analysis. 124 compounds were screened in Formula 9002A, and four constituents including salidroside, gastrodin, niacinamide and umbelliferone were screened as potential active components for treatment of AD by network pharmacology. Among them, salidroside and gastrodin showed higher relevant with AD targets, such as ESR1 and AR. The pharmacokinetic study showed that they could be absorbed and identified in plasma, the half-life and mean residence times of salidroside and gastrodin in plasma were nearly increased 2-fold by administration of Formula 9002A compared with those by administration of monomer, indicating the extended action time of active compounds in vivo. Formula 9002A exerted the efficacy in the treatment of AD mainly by regulating the APP, GSK3β, ESR1, AR targets based on the anti-β-amyloid protein deposition, anti-oxidation and anti-apoptosis pathways. Two genes enriched in Alzheimer's disease pathway, APP and GSK3β, were further validated. The experiments also demonstrated that Formula 9002A could down-regulated APP and GSK3β protein expression in model mice brain and improved their cognitive ability. In summary, Formula 9002A has the characteristics of multiple targets and multiple pathways in the treatment of AD and salidroside and gastrodin might be the main active constituents, which could provide a foundation for further research and application.